Հարկ վճարող կազմակերպությունների կարգավիճակը - Թամարա Գրիգորյան (ՀՀ ԳԱԱ հրատ.)
В данной научной статье проанализировано правовое положение (статус) платящих налог компаний, классифицированы их права и обязанности, отделены некоторые элементы характеризующие их, перечислены случаи прекращения действия таких организаций, раскрыты основы и виды их юридической ответственности, основания для освобождения от ответственности. This scientific article analyzes the legal status of taxpaying companies, classifies their legal liability. Some of their definite characterizing features are segregated. Closing cases of such companies are enumerated. Moreover, the theories and types of their legal liability and the grounds for exemption from liability are as well revealed.
Keywords: Revenue; Taxation; Internal Revenue; Law